2020
DOI: 10.3390/ijms21249400
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Epstein–Barr-Virus-Associated Gastric Cancer Correlated with Prognostic Classification and Development of Therapeutic Options

Abstract: Gastric cancer (GC) is a deadly disease with poor prognosis that is characterized by heterogeneity. New classifications based on histologic features, genotypes, and molecular phenotypes, for example, the Cancer Genome Atlas subtypes and those by the Asian Cancer Research Group, help understand the carcinogenic differences in GC and have led to the identification of an Epstein–Barr virus (EBV)-related GC subtype (EBVaGC), providing new indications for tailored treatment and prognostic factors. This article prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 177 publications
(210 reference statements)
0
10
0
Order By: Relevance
“…Additionally, Helicobacter pylori (H. pylori) and Epstein-Barr virus (EBV) are the main risk factors for GC development [1,2]. Nevertheless, the distribution of histological subtypes of GC and the frequencies of H. pylori-and EBV-related GC vary worldwide [4][5][6]. The genetic diffuse GC accounts for approximately 1-3% of GC cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Helicobacter pylori (H. pylori) and Epstein-Barr virus (EBV) are the main risk factors for GC development [1,2]. Nevertheless, the distribution of histological subtypes of GC and the frequencies of H. pylori-and EBV-related GC vary worldwide [4][5][6]. The genetic diffuse GC accounts for approximately 1-3% of GC cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Epstein–Barr virus represents the most thoroughly researched gamma‐herpes virus, as well as the prototypical lymphocryptoviral 54 . The first virus to be proven to cause cancer in humans is EBV, a double‐stranded DNA virus from the herpesvirus family 55 . Multiple investigations and systematic analyses have demonstrated that having a history of infectious mononucleosis (IM) substantially raises the possibility of developing MS and that people who are EBV seropositive are more likely to develop MS, especially if they have antibodies against the EBV Nuclear Antigen 1 (EBNA‐1) and Viral Capsid Antigen proteins 56 .…”
Section: Discussionmentioning
confidence: 99%
“…EBVaGCs are reported to be correlated with lower T and N stages, outlining a better prognosis than the EBER-ISH negative cases, especially during the early stage in the submucosa [38]. However, these findings are contradicted by other papers which highlight no differences in survival between EBVaGC and EBV-negative gastric carcinoma (EBVnGC) cases after surgery and/or conventional chemotherapy [39]. In our series, Kaplan-Meier curves showed that EBER-ISH positive cases have significantly better overall survival (OS) than EBER-ISH negative cases.…”
Section: Survival Analysismentioning
confidence: 91%